Idhu en niram!இது என் நிறம்! - Nancy Raj,Jeeva Raghunath (Tulika, 2020)
Children's story based on various colours.
Children's story. - Translated from English. - Translation of: It's my colour
Keywords: Colors; Juvenile fiction.; Colors; Pictorial works; Juvenile fiction.; Children's stories; Indic (English); Translations into Tamil.; Children's stories; Indic (English); Pictorial works; Translations into Tamil.